Is the Femoro-Epiphyseal Acetabular Roof (FEAR) index on MRI a relevant predictive factor of instability in a borderline dysplastic hip?. (November 2019) - Batailler, Cécile; Weidner, Jan; Wyatt, Michael; Pfluger, Dominik; Beck, Martin
Abstract : Aims: A borderline dysplastic hip can behave as either stable or unstable and this makes surgical decision making challenging. While an unstable hip may be best treated by acetabular reorientation, stable hips can be treated arthroscopically. Several imaging parameters can help to identify the appropriate treatment, including the Femoro-Epiphyseal Acetabular Roof (FEAR) index, measured on plain radiographs. The aim of this study was to assess the reliability and the sensitivity of FEAR index on MRI compared with its radiological measurement. Patients and Methods: The technique of measuring the FEAR index on MRI was defined and its reliability validated. A retrospective study assessed three groups of 20 patients: an unstable group of 'borderline dysplastic hips' with lateral centre edge angle (LCEA) less than 25° treated successfully by periacetabular osteotomy; a stable group of 'borderline dysplastic hips' with LCEA less than 25° treated successfully by impingement surgery; and an asymptomatic control group with LCEA between 25° and 35°. The following measurements were performed on both standardized radiographs and on MRI: LCEA, acetabular index, femoral anteversion, and FEAR index. Results: The FEAR index showed excellent intraobserver and interobserver reliability on both MRI and radiographs. The FEAR index was more reliable on radiographs than on MRI. The FEAR index on MRI was lower in the stable borderline group (mean -4.2° (sd 9.1°)) compared with the unstable borderline group (mean 7.9° (sd 6.8°)). With a FEAR index cut-off value of 2°, 90% of patients were correctly identified as stable or unstable using the radiological FEAR index, compared with 82.5% using the FEAR index on MRI. The FEAR index was a better predictor of instability on plain radiographs than on MRI. Conclusion: The FEAR index measured on MRI is less reliable and less sensitive than the FEAR index measured on radiographs. The cut-off value of 2° for radiological FEAR index predicted hip stability with 90% probability. Cite this article: Bone Joint J 2019;101-B:1578–1584